Answer:
the first one
Step-by-step explanation:
i did the test and got it right
Help with what, unless there is a picture, my phone is glitchy and i cant see pics for sum reason
The answer is <span>f(x) = 2x2 + 3x – 3
</span>
f(x) = ax² + bx + c
a - the leading coefficient
c - the constant term
<u>We are looking for a = 2, c = -3</u>
Through the process of elimination:
The first (f(x) = 2x3 – 3) and the third choice (f(x) = –3x3 + 2) have x³ so these are not quadratic function.
In the function: <span>f(x) = –3x2 – 3x + 2
</span>a = -3
c = 2
In the function: f(x) = 2x2 + 3x – 3
a = 2
c = -3
Answer:
janet can plant 36 per hour Amy can plant 34per hour
Step-by-step explanation:
A) 68.8
b) 5.9
c) 634.9
d) 90.0